A study on understanding consumers’ perception to develop a market for SMART washing powder : a home care product from ACI consumer brands - Rashid, Morsalin (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.